Hubungan Tingkat Pengetahuan dengan Kepatuhan Perawat Dalam Pelaksanaan Discharge Planning Pada Pasien Rawat Inap - Marwah, Marwah; Sulidah, Sulidah (Universitas Malahayati, 2024)
ABSTRACT Discharge planning is the process of planning a patient's discharge from the hospital. Effective discharge planning can reduce the risk of readmission to the hospital and increase public trust in hospital services. Ideally, discharge planning should be carried out collaboratively, with nurses playing a major role. This study aims to identify the level of knowledge and compliance of nurses in implementing discharge planning and to analyze the relationship between the two. This research is an analytic-correlational study with a cross-sectional approach. The study population consisted of all nurses at RSUD dr. H. Jusuf SK who were on duty in the inpatient unit, with a total population of 258 people. The sample size was obtained using the Slovin formula, resulting in 110 respondents selected through purposive sampling. The results of this study identified that nurses' knowledge about discharge planning was categorized as sufficient, with most respondents being compliant in implementing discharge planning. The data analysis using the Chi Square test yielded a p-value of 0.005 < 0.05, indicating a significant relationship between knowledge and compliance in implementing discharge planning with a moderate strength of association.Top of Form Keywords: Discharge Planning, Compliance, Knowledge ABSTRAK Discharge planning merupakan perencanaan pemulangan pasien dari rumah sakit. Discharge planning yang baik dapat mengurangi risiko readmisi ke rumah sakit dan meningkatkan kepercayaan masyarakat terhadap pelayanan rumah sakit. Idealnya discharge planning dilaksanakan secara kolaboratif dengan perawat mempunyai peran besar didalamnya. Penelitian ini bertujuan untuk mengidentifikasi tingkat pengetahuan dan kepatuhan perawat dalam pelaksanaan discharge planning serta menganalisis hubungan keduanya. Penelitian ini merupakan kajian analitic-correlational dengan pendekatan cross-sectional. Populasi penelitian ini adalah semua perawat RSUD dr. H. Jusuf SK yang bertugas di unit rawat inap dengan besar populasi 258 orang. Besar sampel diperoleh dengan rumus Slovin sebesar 110 responden yang diambil dengan teknik purposive sampling. Hasil penelitian ini teridentifikasi pengetahuan perawat tentang discharge planning pada kategori cukup dengan sebagian besar responden patuh melaksanakan discharge planning. Analisis data menggunakan uji Chi Square diperoleh p-value sebesar 0,005 < 0,05 sehingga dapat disimpulkan ada hubungan yang bermakna antara pengetahuan dan kepatuhan pelaksanaan discharge planning dengan kekuatan hubungan sedang. Kata Kunci: Discharge Planning, Kepatuhan, Pengetahuan